(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2021)
Towards the end of the 19th century, in much of the world, the emergence of the Nation States has demanded a legitimizing role from History in the conformation of a collective identity and in the search for the consolidation of its origins, resulting in myths, practices and functional speeches to him. In this scenario, the school was always a propitious place to accompany the nationalist foundations materialized in the commemorations, the orientations of the curriculum, school manuals or ritual acts. In this sense, the different conceptions of History in general, and nationalist ideals in particular, take on relevance in the training of teachers and in teachers. In Argentina, and the world, the ephemeris survive as immutable, establishing in the collective imagination certain romantic ideas and historical myths about the national history, which even last until the stage of initial teacher training and their first years of work. This paper seeks to make visible the partial results of a broader investigation that came close to recognizing those mythical and romantic conceptions most deeply rooted in the trainee teachers in early childhood and primary education, and teachers.